Understanding feelings about breast cancer: nurses’ report - Soraya Bezerra Furtado; Sâmya Aguiar Lôbo; Míria Conceição Lavinas Santos; Anna Paula Sousa da Silva; Ana Fátima Carvalho Fernandes (Rev Rene)
The aim of this study was to understand the feelings of the oncology nurses about breast cancer. It was a qualitative research through which eight (8) nurses were interviewed during the months of November and December 2006. The interview was of the semi-structured kind, with the following guiding questions: How do you feel about the possibility of having breast cancer? A comprehensive analysis of the interviews revealed some categories: including feelings about breast cancer, the stigma of the disease and mutilation, disease and treatment, the femininity and sexuality as well as acceptance of the disease. It was concluded that the fact of being a health professional, specifically in oncology, does not mean that the individual demonstrates a better way of facing the supposed disease, since it is evidenced the presence of the stigma in the consolidated lines of the participants.